DEVELOPMENT OF CHILDREN WITH SPECIAL NEEDS IN PRESCHOOL AGE - Rimbayeva Ozoda Bazarbayevna (Western European Studies, 2024)
the preschool age period plays an important role in a person's life. During this period, the child receives a lot of information. This article provides the necessary recommendations for the development of children with special needs in preschool age.
Keywords: development; game; training